Immigration within European Union - Does health immigration make a difference in analgesic use? - Airaksinen M.; Pietilä K; Väänänen MH (Centro de Investigaciones y Publicaciones Farmaceuticas, 2006)
European integration has facilitated the emigration inside Europe and it has been predicted that the amount of immigrants in Southern European countries will increase in the future. As these people age and their morbidity increases, they will demand more services from local health care than immigrants do at the moment. The aim of this study is to determine the amount of Finnish people who have moved to Spain for health reasons (health immigrants) and whether their health service and analgesic usage patterns differed from those of non-health immigrants. Methods: This study was carried out among Finnish people living in Costa del Sol area, southern Spain. The data were collected by questionnaire during 2002 by using a convenience sample of 1,000 Finns living permanently in the area (response rate 53%, n=530). Statistical analyses were conducted using statistical software SPSS 11.5.Results: Two-thirds of the respondents were categorised as health immigrants. Health immigrants were more often suffering from chronic morbidity, their perceived health status was poorer and they used public health services more often than the non-health immigrants. Half (50%) of the all respondents had used some analgesics during the two weeks before the survey. There were more analgesic users among the health immigrant group (54 % vs. 43 %, p = 0.034) and they also used analgesics more frequently than the non-health immigrants (27 % vs. 9 %, p= 0.020). Conclusions: Our study indicates, that high amount of Finnish immigrants suffer from some degree of health problems and the health state factors have a large influence on the emigration into Spain. As this kind of trend might also exist among immigrants from other EU-nations, immigrants might burden the local Spanish health care services in the future. Therefore the Providers of health care services in immigrant areas should consider these trends in planning health care in the future.